2023
DOI: 10.3390/su15021259
|View full text |Cite
|
Sign up to set email alerts
|

Interactions between Health and the Sustainable Development Goals: The Case of the Democratic Republic of Congo

Abstract: A systematic and contextualized assessment of the interactions between the Sustainable Development Goals and health in the Democratic Republic of Congo is currently lacking. This study aimed to characterize and classify the linkages between the Sustainable Development Goals in the DRC with a focus on health and well-being. In this semi-qualitative participatory study, 35 experts assessed 240 interactions between 16 of the 17 SDGs during a two-day workshop in Kinshasa, Democratic Republic of the Congo, using a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 23 publications
1
2
0
Order By: Relevance
“…Despite the multitude of challenges, Somalia has made progress on improving the health and well-being in the country [ 35 ]. Similarly to other analyses of the linkages between health and the SDGs [ 20 , 36 , 37 ], we found that improving good health and well-being can enable progress on other SDGs. Conversely, health was deemed to be relying on the development of other sectors possibly due to the chronic instability of Somalia and relatively underdeveloped other sectors.…”
Section: Discussionsupporting
confidence: 83%
“…Despite the multitude of challenges, Somalia has made progress on improving the health and well-being in the country [ 35 ]. Similarly to other analyses of the linkages between health and the SDGs [ 20 , 36 , 37 ], we found that improving good health and well-being can enable progress on other SDGs. Conversely, health was deemed to be relying on the development of other sectors possibly due to the chronic instability of Somalia and relatively underdeveloped other sectors.…”
Section: Discussionsupporting
confidence: 83%
“…Peace and tranquillity are undoubtedly essential components for ensuring the health and welfare of a population. The amalgamation of SDG 3 (on attaining healthy lives and promoting well-being), SDG 16 (towards peace, justice, and building strong institutions), and SDG 17 (partnership for goals) is imperative to enable resilient health systems in conflict settings [108,109].…”
Section: Discussionmentioning
confidence: 99%
“…The WHO contends that within a comprehensive strategy towards achieving SDGs, health and well-being are key indicators of success towards accomplishing the SDGs [54]. The progress on SDG-3 is deemed to promote progress on the other SDGs, and this is a reciprocated effect [58]. More specifically, there are high to moderate positive correlations between SDG-3 and other SDGs relating to economic development, including human capital development, infrastructure development, and equitable society [6,59,60].…”
Section: Health and Well-being As Sdg: Significance And Progressmentioning
confidence: 99%